INTEGRATION OF IOT TECHNOLOGIES INTO CNC MACHINING SYSTEMS: A CASE STUDY PERSPECTIVE FOR UZBEKISTAN’S MANUFACTURING SECTOR (International journal of artificial intelligence, 2026)
As Uzbekistan accelerates its transition towards an industrialized digital economy under the "Digital Uzbekistan 2030" strategy, modernizing existing manufacturing assets has become crucial. This paper analyzes the integration of Internet of Things (IoT) technologies into Computer Numerical Control (CNC) machining systems, focusing on local industrial contexts such as automotive and agricultural machinery production. While traditional CNC machines offer precision, they often lack connectivity. This study proposes a low-cost IoT architecture to monitor spindle load, vibration, and energy usage. Comparative analysis suggests that IoT integration can reduce unplanned downtime by 20-25% and optimize energy consumption by 12-15%. The findings provide a roadmap for Uzbek manufacturers to upgrade legacy equipment to Industry 4.0 standards cost-effectively.